Mitochondrial bioenergetic function and metabolic plasticity in stem cell differentiation and cellular reprogramming - Chen, Chien-Tsun; Hsu, Shu-Han; Wei, Yau-Huei (Biochimica et biophysica acta, 2012)
The self-renewal ability and pluripotent differentiation potential of stem cells hold great promise for regenerative medicine. Many studies focus on the lineage-specific differentiation and expansion of stem cells, but little is known about the regulation of glycolysis and mitochondrial biogenesis and function during these processes. Recent studies have demonstrated a strong correlation between cellular metabolism and the pluripotency and differentiation potential of stem cells, which indicates the importance of bioenergetic function in the regulation of stem cell physiology. We summarize recent findings in the control of stem cell competence through the regulation of bioenergetic function in embryonic, hematopoietic, mesenchymal, and induced pluripotent stem cells, and discuss the up-to-date understanding of the molecular mechanisms involved in these biological processes. It is believed that the metabolic signatures are highly correlated with the stemness status (high glycolytic flux) and differentiation potential (mitochondrial function) of stem cells. Besides, mitochondrial rejuvenation has been observed to participate in the reprogramming process. Understanding the metabolic regulation of stem cells will have great value in the characterization and isolation of stem cells with better differentiation potential. It also provides novel strategies of metabolic manipulation to increase the efficiency of cellular reprogramming. This article is part of a Special Issue entitled Biochemistry of Mitochondria, Life and Intervention 2010. ► We summarize recent findings in the metabolic control of stem cell competence. ► Mitochondrial activity is highly associated with ESC pluripotency. ► Mitochondrial activity and ROS signaling are important for HSC self-renewal. ► Mitochondrial activity and ROS scavenging are crucial for MSC differentiation. ►Mitochondria undergo rejuvenation during cellular reprogramming.